PENGARUH PUPUK ORGANIK CAIR BERBAHAN DASAR LIMBAH SAWI PUTIH (Brassica chinensis L.) TERHADAP PERTUMBUHAN TANAMAN JAGUNG MANIS - Rahmah, Atikah; Izzati, Munifatul; Parman, Sarjana (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2014)
Liquid organic fertilizer was a fertilizer that comes from nature and served to increase the physical, chemical and biological condition of soil. It contains nutrient that be able to improve plants growth. The purpose of this experiment was to observe the effect of liquid organic fertilizer from waste of china cabbage on the growth of sweet corn. The research was conducted in Laboratory of Biology, Diponegoro University. The research design used was a completely randomized design witha single factor, namely Â the concentration of liquid organic fertilizer in 6 treatments and 5 replication that. The treatments were control (without fertilizer), 1 mL/L, 2 mL/L, 3 mL/L, 4 mL/L, 5 mL/L. The data were analyzed by Analysis of Variance (ANOVA) at 95% significance level. Parameters observed were plant height, number of leaves, fresh weight and dry weight. The results showed that treatment of liquid organic fertilizer spraying with different concentrations affect on all growth parameters. Concentration of 3 mL/L produced the highest plant, the concentration of 1 mL/Land 4 mL/L Â resulted in the highest number of leaves. The highest of fresh and dry weight were resulted by application of 1 mL/L liquid organic fertilizer.